Cost analysis of glatiramer acetate vs. fingolimod for the treatment of patients with relapsing-remitting multiple sclerosis in Spain - Sanchez-de la Rosa, Rainel (Springer, 2013)
BACKGROUND: Fingolimod is an innovative drug with a significant budget impact in the treatment of MS in Spain. The aim of this study was to calculate the direct cost comparison of glatiramer acetate and fingolimod for the treatment of patients with relapsing-remitting multiple sclerosis (RRMS) in Spain. METHODS: A cost analysis model was developed to compare glatiramer acetate and fingolimod, based on a 1-year time horizon. In addition to the pharmacological costs, resource use was estimated for glatiramer acetate (1 hour of training with nursing staff in self-injection techniques for subcutaneous administration) and fingolimod (vaccination for varicella-zoster virus in 5% of patients, 3 complete blood counts per year, 3 ophthalmology visits for prevention of macular edema, 3 transaminase tests to monitor liver function, and cardiovascular monitoring consisting of 1 ECG before the first fingolimod dose and at 6 hours; 1 day outpatients-hospital visit for cardiological monitoring during 6 hours on the day of the first fingolimod dose, with follow-up of blood pressure and heart rate every hour). The pharmacological costs were calculated based on the ex-factory price of the drugs evaluated, using the doses recommended in the respective Summary of Products Characteristics (SmPC). Total invoicing volume was discounted by 7.5%, as laid down in Spanish Royal Decree 8/2010. Unit costs were obtained from the e-Salud database and the drug catalog. Costs in the model are expressed in €2012. RESULTS: The cost of annual treatment was €9,439.42 for glatiramer acetate and €19,602.18 for fingolimod, yielding a cost difference of €10,162.76. Assuming a fixed budget of €100,000.00, approximately 10 patients could be treated with glatiramer acetate, compared to 5 with fingolimod. CONCLUSIONS: Fingolimod therapy requires twice the investment as glatiramer acetate.